Remote Routing Approach to Restricted Devices in MANETs - Melo, Rodrigo; Aschoff, Rafael R.; Sadok, Djamel; Feitosa, Eduardo (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
Emergency rescue communication systems are designed to provide ubiquitous collaboration among mobile devices without the need for a fixed infrastructure by using mobile ad hoc networks (MANETs). In emergency and rescue operations, MANETs are naturally formed by devices with different processing and communication capabilities. In this scenario, low power devices may become overwhelmed with the control overhead and resulting additional processing required to provide reliable communications among these heterogeneous parties. In this paper we propose a strategy where resource constrained devices can offload part of the routing process to more capable devices participating in the network. Our proposal have been tested and validated in different scenarios. The results show how the proposed approach can successfully reduce the network overhead without significantly reducing the routing process efficiency.